Reviews of Books (International review of mission, 1951)
MUSLIM SOCIETY AND WESTERN INFLUENCE: Islamic Society and the West. By H. A. R. Gibb and Harold Bowen. THE JEWS AND THE PERSON OF JESUS: The Jewish People and Jesus Christ. By Jacób Jocz. THE MESSAGE OF BERDYAEV: Nicolas Berdyaev, Captive of Freedom. By Matthew Spinka. PRIMITIVE LITURGIES: A Critical Study of Primitive Liturgies, Especially that of St James. By K. N. Daniel. THE SUPREME BEING IN AFRICA: African Ideas of God. A Symposium. Edited by Edwin W. Smith. RELIGION IN WEST AFRICA: West African Religion. Illustrated from the Beliefs and Practices of the Yoruba, Ewe, Akan and Kindred Peoples. By Geoffrey Parrinder. THE CHINESE CONCEPTION OF RELIGION: Religion in China. By E. R. Hughes and K. Hughes. NON-CHRISTIAN FAITHS: The Religions of the World. By Godfrey E. Phillips. THE STUDY OF RELIGION: Gott und Mensch. By Gustav Mensching. THE STUDY OF RELIGION: Soziologie der Religion. By Gustav Mensching. THE STUDY OF RELIGION: Religion, Rasse und Christentum. By Gustav Mensching. CITIZENSHIP TRAINING IN THE Y.M.C.A.: Young People and World Citizenship. A Study of Citizenship Attitudes and Programs of Young Adults in Y.M.C.A's. By Glen L. Heathers. GIRLS' EDUCATION IN INDIA: A Larger Way for Women. Aspects of Christian Education for girls in South India. 1717–1948. By K. Nora Brockway.